2018
DOI: 10.1007/s13205-018-1459-9
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and biochemical analyses reveal the mechanism of double-color formation in Paeonia suffruticosa ‘Shima Nishiki’

Abstract: Paeonia suffruticosa 'Shima Nishiki' is a very precious double-color cultivar because of its distinctive and colorful flowers. However, our understanding of the underlying mechanisms of its double-color formation is limited. The present study investigated the soluble sugar content, cell sap pH value and anatomical structure, anthocyanin composition and content and expression patterns of genes related to anthocyanin biosynthesis in the red and pink petals of the 'Shima Nishiki' cultivar. Here, we found that sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…L. longiflorum with a yellow anther lacks anthocyanin in its petals and anther due to DFR mutation [74]. Research on the two-color Chinese herbaceous peony has demonstrated that the significant differential expression of PsDFR might play an important role in the development of the two colors in this plant [75].…”
Section: Dihydroflavonol 4-reductasementioning
confidence: 99%
“…L. longiflorum with a yellow anther lacks anthocyanin in its petals and anther due to DFR mutation [74]. Research on the two-color Chinese herbaceous peony has demonstrated that the significant differential expression of PsDFR might play an important role in the development of the two colors in this plant [75].…”
Section: Dihydroflavonol 4-reductasementioning
confidence: 99%
“…The expression patterns of some flower-color variation in plants were similar with 'Vivian'. Differences in LBG expression caused color differences in bicolor peony "Shima Nishiki" [75], pink camellia [76], and yellow/orange variation in Gentiana [77]. Therefore, the expression of LBGs can affect the pigmentation in these plants.…”
Section: Lvmyb5 and Lvmyb7 Are Synergistically Regulators Of Anthocyamentioning
confidence: 99%
“…Flavonoids are very important pigments that extensively affect flower color. Among them, anthocyanins contribute the most (Davies et al, 2012;Grotewold, 2006;Nishihara and Nakatsuka, 2011;Wang et al, 2021;Zhang et al, 2018aZhang et al, , 2018b. In addition to anthocyanins, many physiological factors, such as vacuolar pH value (Quattrocchio et al, 2006;Yoshida et al, 2005), metal element content (Schreiber et al, 2011;Shoji et al, 2010), upper epidermal cell shape (Baumann et al, 2007;Deng et al, 2022;Noda et al, 1994;Zhang et al, 2018b), and soluble sugar content (Zhang et al, 2015;Zheng et al, 2009), can also affect the presentation of flower color to a certain extent.…”
Section: Physiological Factors Affecting the Color Difference Of Doub...mentioning
confidence: 99%